Strontium isotopes (87Sr/86Sr) reveal the life history of freshwater migratory fishes in the La Plata Basin. (21st September 2020) - Avigliano, Esteban; Pouilly, Marc; Bouchez, Julien; Domanico, Alejandro; Sánchez, Sebastian; Llamazares Vegh, Sabina; Clavijo, Cirsthian; Scarabotti, Pablo; Facetti, Juan F.; Caffetti, Jacqueline D.; del Rosso, Franco R.; Pecheyran, Christophe; et al.
Abstract: Strontium isotopes ( 87 Sr/ 86 Sr) were evaluated as a potential method for studying the geographical origin of populations and movements patterns of migratory fish from the La Plata Basin (Paraná, Uruguay and Bermejo Rivers and Río de la Plata Estuary, South America). Surface water samples were collected at 43 sites during austral summer and winter (2018) while, Surubí ( Pseudoplatystoma corruscans ), Patí ( Luciopimelodus pati ), dorado ( Salminus brasiliensis ) and sábalo ( Prochilodus lineatus ) fishes were collected at seven locations. Water 87 Sr/ 86 Sr ratio was analysed by MC‐ICP‐MS ( N = 74) and otolith core‐to‐edge 87 Sr/ 86 Sr transects ( N = 50) were measured by LAfs‐MC‐ICP‐MS. Several water bodies presented significantly different ( p < 0.05) water 87 Sr/ 86 Sr values. A 1:1 relationship was found between 87 Sr/ 86 Sr measured in edge otolith and water. Data provide novel perspectives about migratory behaviour for all species, such as potential cross‐border migrations between countries of more than 1, 000 km recorded for L. pati, S. brasiliensis and P. lineatus . These species seem to move between the Paraná and Uruguay rivers, which imply using the delta or the estuary as a corridor between them. Discriminant analysis based on otolith core 87 Sr/ 86 Sr suggested that the four species studied originate in sub‐basins different from those that were collected and revelled the presence of several potential spawning/nursery areas. The otolith 87 Sr/ 86 Sr profiles also suggested movements between different environments such as reservoirs, large plain rivers, mountain streams, floodplain valleys and estuaries. These results show the potential of 87 Sr/ 86 Sr as a tool for tracking the life history of fishes, and depict for the first time a complex use of the La Plata basin by the fishes, providing new information for management plans at the regional level.